2021
DOI: 10.3233/prm-190628
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of elimination disorders and comorbid psychiatric disorders in Iranian children and adolescents

Abstract: PURPOSE: Currently, there is a paucity of studies on the prevalence of Elimination Disorders among Iranian children and adolescents. Due to the ongoing need to monitor the health status of these children and adolescents, the present study aims to investigate the prevalence of Elimination Disorders and comorbid disorders in Iranian children and adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
3
1
Order By: Relevance
“…In this study, the total magnitude of elimination disorders was 16.8%, which is consistent with a similar study conducted in Germany (14.8%), Australia (18.2%), Egypt (15.7%), and Kenya (14.5%) (23,30,39,41). However, the magnitude of elimination disorder in this study is higher than the studies conducted in Iran (5.4%), the United States (4.45%), and Hong Kong (3.1%) (27)(28)(29). The possible reason for the difference between the Iran study and the current study is that the former was done in the community among children age 6-18 years and used the Kiddie-Schedule for Affective Disorders and Schizophrenia for School-Age Children-Present and Lifetime Version (K-SADS-PL DSM-IV) to discriminate elimination disorders, whereas the present study is hospital-based among children and adolescents aged 5-14 years and used the DSSDES tool and DSM-5 to identify elimination disorders.…”
Section: Discussioncontrasting
confidence: 83%
“…In this study, the total magnitude of elimination disorders was 16.8%, which is consistent with a similar study conducted in Germany (14.8%), Australia (18.2%), Egypt (15.7%), and Kenya (14.5%) (23,30,39,41). However, the magnitude of elimination disorder in this study is higher than the studies conducted in Iran (5.4%), the United States (4.45%), and Hong Kong (3.1%) (27)(28)(29). The possible reason for the difference between the Iran study and the current study is that the former was done in the community among children age 6-18 years and used the Kiddie-Schedule for Affective Disorders and Schizophrenia for School-Age Children-Present and Lifetime Version (K-SADS-PL DSM-IV) to discriminate elimination disorders, whereas the present study is hospital-based among children and adolescents aged 5-14 years and used the DSSDES tool and DSM-5 to identify elimination disorders.…”
Section: Discussioncontrasting
confidence: 83%
“…Specifically, seven studies within the dataset investigated ADHD prevalence across a wider age spectrum, ranging from 5 to 18 years. Interestingly, the reported prevalence for these studies was extremely high, ranging between 32% and 40% 35 45 57 58 60 62 71 82. Furthermore, we observed that studies using different versions of the DSM show varying prevalence rates.…”
Section: Discussionmentioning
confidence: 76%
“…Finally, 63 articles involving 849 902 participants were included in the meta-analysis (as shown in PRISMA, figure 1). 35–97 The studies and participant characteristics are reported in online supplemental table S2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation